(untitled) (Aporte Santiaguino, 2024)
Through an examination of the Theory of Seismic Energy and the Theory of Volcanic Energy, we come to comprehend that the interplay of internal and external energies in conducive terrain has led to immeasurable transformations, assessable within geological time frames. Consequently, this study posits that the intricate evolution of Earth’s crust relief stems from the inverse shift in elevations and the mobility of oceanic water masses. This, in turn, influences the location, size, shape, and quantity of continents, islands, and oceans. It is crucial to recognize that the geographical features we currently observe merely capture a momentary snapshot, due to the constant movement of the Earth’s surface.